Pengaruh Kerapatan Tanaman terhadap Pertumbuhan dan Hasil Benih Kentang (Solanum Tuberosum L.) Generasi Satu (G1) Varietas Granola - Fatchullah, Deden (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2017)
The experiment was conducted in Experimental Research Station of Indonesian Institute for Vegetable Research (IIVR) at Cikole, Lembang city, West Bandung in September to December 2015. The research area was located in 1250 m above sea level with the type of soil is Andosol, and type of climate is B (Wet). The objective of this experiment was to find out the effect of plant spacing on the growth and the quality of potato seed (Solanum tuberosum L. var granola) of the first generation (G1). The experiment was arranged in a randomized block design (RBD) with a single factor. The treatment was 4 types of plant spacing: A1 (5 cm x 5 cm), A2 (6 cm x 6 cm), A3 (7 cm x 7 cm) and A4 (8 cm x 8 cm). The result showed that the plant spacing was significantly affecting on plant height and plant canopy at 21 days after planting (DAP), and percentage of germination at 63 DAP. It was determined that A1 plant spacing (5cm x 5cm) provide the highest plant (15.11 cm) and highest plant canopy (10.40 cm) at 21 DAP, and A4 plant spacing (8cm x 8cm) present the highest of a percentage of germination (27,34%).